Threatened identity: Ezra, Nehemiah, and Christian nationalism in the United States - Hernández-Marcial, Lydia (2024)
The diversity of voices in the Bible and the variety of contexts of its interpreters makes biblical interpretation challenging. This challenge opens the door to opposing interpretations of the same biblical passage, depending on each group’s viewpoint. Choon-Leong Seow refers to the history of biblical interpretation as a “history of consequences,” both what comes after the Bible and results of biblical interpretation and reception. Considering the diversity of approaches to the Scriptures, readers need to be aware that every interpretation will have a consequence. Knowing that Christian nationalism uses Bible passages and Christian language to justify its discourse, this article considers the problems, and consequences, of applying Ezra 9–10 and Neh 13:32–37 to support xenophobia and racism when addressing the subject of immigration in the United States. First, the article defines Christian nationalism and offers an introduction to Ezra–Nehemiah’s post-exilic background, including examples of the complexities of Judah’s colonial status. Second, the article analyzes the expulsion of the “foreign” wives and children in Ezra 9–10 and Neh 13:23–30 and its relationship with identity formation. The essay ends by offering alternative voices within the Hebrew Bible/Old Testament canon.
Keywords: Xenophobia; Racism; Post-exilic; Nehemiah 13; Identity; Ezra 9–10; Christian Nationalism; Biblical Interpretation